Gender, religion, and family law : theorizing conflicts between women's rights and cultural traditions - Joffe, Lisa Fishbayn; Neil, Sylvia (Brandeis series on gender, culture, religion, and law, 2012)
"In many regions of the world, rights guaranteed under the civil law, including rights to gender equality within marriage and rights in the distribution of family property and child custody upon divorce, are in conflict with the principles of religious law. Women's rights issues are often at the heart of these tensions, which present pressing challenges for theorists, lawyers, and policymakers. This anthology brings together leading scholars and activists doing innovative work in Jewish law, Muslim law, Christian law, and African customary law. Using examples drawn from a variety of nations and religions, they interrogate the utility of recent theoretical models for engaging with gender and multicultural conflicts, explore contextual differences, and analyze and celebrate stories of successful initiatives that have transformed legal and cultural norms to improve women's lives" --